Manufacturing process of ultra-thin copper foil with high mechanical property

By adding high-resistance high-delay series additives and performing oxygen-free heat treatment in the copper foil manufacturing process, the problem of insufficient mechanical properties of extremely thin copper foils is solved, and the high tensile strength and elongation are improved.

CN119553321APending Publication Date: 2025-03-04JIANGXI HUAXIN MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510119812.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing extremely thin copper foils have shortcomings in terms of mechanical properties, and their tensile strength and elongation are low, making it difficult to meet the needs of high-energy-density lithium-ion batteries.

Method used

By adding high-resistance series of additives, including brighteners, leveling agents, wetting agents and grain refining agents in the copper foil manufacturing process, and performing heat treatment processes in an oxygen-free environment, the internal grain morphology and tissue structure of the copper foil are optimized.

Benefits of technology

The tensile strength and elongation of copper foil are significantly improved, the internal grain morphology and structural structure are optimized, and the mechanical properties of copper foil are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553321A_ABST
    Figure CN119553321A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing process of an ultra-thin copper foil with high mechanical property, which comprises the following steps: S1, putting a treated copper wire into a copper dissolving tank, then adding a proper amount of sulfuric acid into the copper dissolving tank for reaction to obtain a copper sulfate electrolyte, and carrying out a series of filtration, impurity removal and purification on the obtained copper sulfate electrolyte to obtain an ultra-thin copper foil with high mechanical property; and pure copper sulfate electrolyte is obtained. The brightening agent, the leveling agent, the wetting agent and the grain refiner with proper proportions are added in the manufacturing process of the copper foil, so that the produced copper foil has the performance of high tensile strength and ductility; and after the copper foil is subjected to heat treatment in an oxygen-free environment in the manufacturing process of the copper foil, the surface of the copper foil is free of oxidation discoloration, and the elongation of the copper foil is further improved, so that the copper foil produced by the process optimizes the internal crystal grain morphology, homogenizes the structure, purifies the crystal boundary, and also improves the mechanical property of the copper foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of production and preparation of ultra-thin copper foil, and in particular to a manufacturing process of an ultra-thin copper foil with high mechanical properties. Background Art

[0002] Copper foil, as the negative electrode current collector of the battery, is one of the key materials for manufacturing lithium-ion batteries. As new energy vehicle batteries develop towards high energy density, higher requirements are placed on the ultra-thinness of copper foil, but the thinner the copper foil, the lower its mechanical properties. The existing production process can only produce ultra-thin copper foil (<6μm) with a tensile strength of ≤340MPa and an elongation of ≤4%.

[0003] The performance of copper foil is related to its microstructure, which can be regulated by the manufacturing process; therefore, the present application can improve the crystallization of copper and control grain growth through a series of high-resistance and high-elongation additives; the high-resistance and high-elongation copper foil heat treatment process can further optimize the internal grain morphology of the copper foil, make the structure uniform, purify the grain boundaries, and improve the mechanical properties of the copper foil. Summary of the invention

[0004] The purpose of the present invention is to provide a manufacturing process for an ultra-thin copper foil with high mechanical properties, which can optimize the internal grain morphology of the copper foil, make the structure uniform, purify the grain boundaries, and improve the mechanical properties of the copper foil.

[0005] The invention provides the following technical solution: a manufacturing process of an extremely thin copper foil with high mechanical properties, comprising the following steps: Step S1: placing the treated copper wire into a copper dissolving tank, then adding an appropriate amount of sulfuric acid into the copper dissolving tank for reaction to obtain a copper sulfate electrolyte, and the obtained copper sulfate electrolyte is subjected to a series of filtration and impurity removal purification to obtain a pure copper sulfate electrolyte; Step S2: adding a series of high-resistance and high-ductility additives to the pure copper sulfate electrolyte and performing a mixing process; Step S3: transporting the mixed copper sulfate electrolyte to a foil production machine for electrolytic foil production; Step S4: an anti-oxidation device is provided during the foil production process of the foil production machine to perform anti-oxidation treatment on the produced copper foil; Step S5: After producing a roll of mother roll copper foil, the roll is placed in an oxygen-free environment for heat treatment; Step S6: The copper foil that has passed the heat treatment process is sent to a slitting machine for slitting.

[0006] Furthermore, in step S2: the high resistance and high ductility series additives include: brightener, leveler, wetting agent and grain refiner.

[0007] Furthermore, the mass concentration ratio of the brightener, the leveler, the wetting agent and the grain refiner is 1:0.2-0.4:0.1-0.3:1-1.5.

[0008] Furthermore, the brightener is an organic substance having a sodium sulfonate group; the organic substance containing a sodium sulfonate group is one of polyisothiourea propanesulfonic acid inner salt, sodium 3-mercapto-1-propanesulfonate, sodium N, N-dimethyldithiocarboxamide propane sulfonate and sodium polydisulfide propane sulfonate.

[0009] Furthermore, the leveling agent is one of a collagen polymer and an amine organic substance.

[0010] Furthermore, the wetting agent is a surfactant such as cellulose, polyether, etc.

[0011] Furthermore, the wetting agent is specifically one of hydroxymethyl cellulose, hydroxyethyl cellulose, diethylene glycol dimethyl ether, ethylene glycol butyl ether and triethylene glycol divinyl ether.

[0012] Furthermore, the grain refiner is one of cyclic sodium disulfide propane sulfonate, phenyl sodium polydisulfide propane sulfonate, rare earth salt, thiourea and thiourea-type organic matter.

[0013] Furthermore, the step S5 specifically includes: after producing a roll of mother roll copper foil, putting it into a heat treatment furnace, making the heat treatment furnace in an oxygen-free environment, and then setting two stages of heat treatment process, and finally slowly cooling it in the heat treatment furnace.

[0014] Furthermore, the two-stage heat treatment process includes: in the first stage, the copper foil is heated to 60°C to 90°C within 3h to 5h, and then the copper foil is kept warm in the heat treatment furnace for 0.5h to 30h; in the second stage, the copper foil is heated to 120°C to 150°C within 3h to 5h, and then the copper foil is kept warm in the heat treatment furnace for 1h to 40h.

[0015] The beneficial effects of the invention are as follows: the invention adds brightener, leveler, wetting agent and grain refiner in appropriate proportions during the manufacturing process of the copper foil, so that the produced copper foil has the properties of high tensile strength and elongation; and in the manufacturing process of the copper foil, after heat treatment in an oxygen-free environment, not only is there no oxidation discoloration on the surface of the copper foil, but the elongation of the copper foil is further improved. Therefore, the copper foil produced by the process of the invention optimizes the internal grain morphology, has a uniform structure, purifies the grain boundaries, and also improves the mechanical properties of the copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the EBSD crystal plane image of the lithium battery copper foil after ordinary heat treatment of the present invention.

[0017] Figure 2 This is the EBSD particle size distribution diagram of the lithium battery copper foil after ordinary heat treatment of the present invention.

[0018] Figure 3 These are IPFs of the lithium battery copper foil with crystal plane index distributed in the normal direction after ordinary heat treatment of the present invention.

[0019] Figure 4 This is the EBSD crystal plane image of the lithium battery copper foil after oxygen-free heat treatment of the present invention.

[0020] Figure 5 This is the EBSD particle size distribution diagram of the lithium battery copper foil after oxygen-free heat treatment of the present invention.

[0021] Figure 6 The IPFs are the IPFs with the crystal plane index of the lithium battery copper foil after oxygen-free heat treatment distributed in the normal direction.

[0022] Figure 7 It is a flow chart of the copper foil manufacturing process of the present invention. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0025] Embodiment 1: Provide a manufacturing process for extremely thin (less than 6 microns) copper foil with high mechanical properties, such as Figure 7 As shown, the following steps are included: Step S1: placing the treated copper wire into a copper dissolving tank, then adding an appropriate amount of sulfuric acid into the copper dissolving tank for reaction to obtain a copper sulfate electrolyte, and the obtained copper sulfate electrolyte is subjected to a series of filtration and impurity removal purification to obtain a pure copper sulfate electrolyte; The concentration of sulfuric acid in the pure copper sulfate electrolyte is 95 g / L to 120 g / L, the concentration of copper ions is 85 g / L to 100 g / L, the concentration of chloride ions is 10 mg / L to 50 mg / L, and the temperature of the copper sulfate electrolyte is 50° C. to 65° C. Step S2: adding a series of high-resistance and high-ductility additives to the pure copper sulfate electrolyte and performing a mixing process; The high-resistance and high-ductility series additives include: brightener, leveler, wetting agent and grain refiner; the brightener is an organic substance containing sodium sulfonate group, specifically one of polyisothiourea propanesulfonic acid inner salt, sodium 3-mercapto-1-propanesulfonate, sodium N, N-dimethyldithiocarboxamide propane sulfonate and sodium polydisulfide propane sulfonate; the leveler is one of collagen polymer and amine organic substance; the wetting agent is a surfactant such as cellulose and polyether, specifically one of hydroxymethyl cellulose, hydroxyethyl cellulose, diethylene glycol dimethyl ether, ethylene glycol butyl ether and triethylene glycol divinyl ether; the grain refiner is one of cyclic sodium disulfide propane sulfonate, sodium phenyl polydisulfide propane sulfonate, rare earth salt, thiourea and thiourea organic substance; Specifically, a brightener, a leveling agent, a wetting agent and a grain refiner are added to a pure copper sulfate electrolyte, so that the pure copper sulfate electrolyte contains 10ppm-12ppm of an additive in the brightener, 2ppm-4.8ppm of an additive in the leveling agent, 1ppm-3.6ppm of an additive in the cellulose class, 1ppm-3.6ppm of an additive in the polyether class, and 10ppm-18ppm of an additive in the grain refiner, and the above additives are mixed with the copper sulfate electrolyte; Step S3: transporting the mixed copper sulfate electrolyte to a foil production machine for electrolytic foil production; Specifically, the mixed copper sulfate electrolyte is transported to a foil machine for electrolytic foil production. After the foil is produced, samples are taken to test whether various physical properties are qualified. If qualified, normal production will be carried out, and if unqualified, adjustments will be made.

[0026] Step S4: an anti-oxidation device is provided during the foil production process of the foil production machine to perform anti-oxidation treatment on the produced copper foil; Specifically, the foil machine is provided with an anti-oxidation device during the foil production process to perform anti-oxidation treatment on the produced copper foil; the anti-oxidation treatment parameters are: pH value 2-4, CrO 3 0.8g / L~1.2g / L, COD2000mg / L~10000mg / L, anti-oxidation liquid temperature 20℃~40℃, anti-oxidation treatment is double-sided chrome plating, and the total chrome content is ≤150ppm.

[0027] Step S5: After producing a roll of mother roll copper foil, the roll is placed in an oxygen-free environment for heat treatment; Specifically, the rolled copper foil is placed in a heat treatment furnace, and the oxygen content in the heat treatment furnace is reduced by inert gas protection or vacuuming to achieve an oxygen-free environment, wherein the oxygen content in the heat treatment furnace is ≤2000ppm, and then a two-stage heat treatment process is set, and finally the foil is taken out after slow cooling in the furnace for 3h to 5h; wherein the two-stage heat treatment process includes: in the first stage, the temperature is raised to 90°C within 3h to 5h, and then the copper foil is kept warm in the heat treatment furnace for 10h; in the second stage, the temperature of the copper foil is raised to 120°C within 3h to 5h, and then the copper foil is kept warm in the heat treatment furnace for 10h; the heating rate in the two-stage heat treatment process is 10°C / h to 100°C / h.

[0028] Step S6: The copper foil that has passed the heat treatment process is sent to a slitting machine for slitting.

[0029] Specifically, the copper foil that has passed the heat treatment is sent to a slitting machine for slitting, and is packaged and put into storage after passing the quality inspection.

[0030] After testing, the raw foil samples were placed in an oven and baked at 150°C for 10 minutes, cut into 100mm×50mm samples with a sampling plate, cut into 4 100mm×15mm strips with a cutting machine, and finally tested for tensile strength and elongation with a universal testing machine; the tensile strength of the copper foil reached 48kgf / mm 2 , the elongation can reach 6%. In this embodiment, the mother roll is placed in an oxygen-free environment for heat treatment after unwinding, and the tensile strength after heat treatment is 47kgf / mm 2 , the elongation reaches 9%.

[0031] Embodiment 2 A process for manufacturing extremely thin copper foil with high mechanical properties, such as Figure 7 As shown, the following steps are included: Step S1: placing the treated copper wire into a copper dissolving tank, then adding an appropriate amount of sulfuric acid into the copper dissolving tank for reaction to obtain a copper sulfate electrolyte, and the obtained copper sulfate electrolyte is subjected to a series of filtration and impurity removal purification to obtain a pure copper sulfate electrolyte; wherein the pure copper sulfate electrolyte has a sulfuric acid concentration of 95g / L-120g / L, a copper ion concentration of 85g / L-100g / L, a chloride ion concentration of 10g / L-50mg / L, and a temperature of the copper sulfate electrolyte of 50°C-65°C.

[0032] Step S2: adding a series of high-resistance and high-ductility additives to the pure copper sulfate electrolyte and performing a mixing process; Specifically, a brightener, a leveling agent, a wetting agent and a grain refiner are added to a pure copper sulfate electrolyte, so that the pure copper sulfate electrolyte contains 10ppm-12ppm of an additive in the brightener, 2ppm-4.8ppm of an additive in the leveling agent, 1ppm-3.6ppm of an additive in the cellulose class, 1ppm-3.6ppm of an additive in the polyether class, and 10ppm-18ppm of an additive in the grain refiner, and the above additives are mixed with the copper sulfate electrolyte; Step S3: transporting the mixed copper sulfate electrolyte to a foil production machine for electrolytic foil production; Specifically, the mixed copper sulfate electrolyte is transported to a foil machine for electrolytic foil production. After the foil is produced, samples are taken to test whether various physical properties are qualified. If qualified, normal production will be carried out, and if unqualified, adjustments will be made.

[0033] Step S4: an anti-oxidation device is provided during the foil production process of the foil production machine to perform anti-oxidation treatment on the produced copper foil; Specifically, the foil machine is provided with an anti-oxidation device during the foil production process to perform anti-oxidation treatment on the produced copper foil; the anti-oxidation treatment parameters are: pH value 2-4, CrO 3 0.8g / L~1.2g / L, COD2000mg / L~10000mg / L, anti-oxidation liquid temperature 20℃~40℃, anti-oxidation treatment is double-sided chrome plating, and the total chrome content is ≤150ppm.

[0034] Step S5: producing a roll of mother roll copper foil, and placing it in an oxygen-free environment for heat treatment after unwinding; Specifically, the rolled copper foil is placed in a heat treatment furnace, and the oxygen content in the heat treatment furnace is reduced by inert gas protection or vacuuming to achieve an oxygen-free environment, wherein the oxygen content in the heat treatment furnace is ≤2000ppm, and then a two-stage heat treatment process is set, and finally the foil is taken out after slow cooling in the furnace for 3 to 5 hours; wherein the two-stage heat treatment process includes: in the first stage, the temperature is raised to 90°C within 3 to 5 hours, and then the copper foil is kept warm in the heat treatment furnace for 10 hours; in the second stage, the temperature of the copper foil is raised to 130°C within 3 to 5 hours, and then the copper foil is kept warm in the heat treatment furnace for 10 hours; the heating rate in the two-stage heat treatment process is 10°C / h to 100°C / h.

[0035] Step S6: The copper foil that has passed the heat treatment process is sent to a slitting machine for slitting.

[0036] Specifically, the copper foil that has passed the heat treatment process is sent to a slitting machine for slitting, and is packaged and put into storage after passing the quality inspection.

[0037] After testing, the raw foil samples were placed in an oven and baked at 150°C for 10 minutes, cut into 100mm×50mm samples with a sampling plate, cut into 4 100mm×15mm strips with a cutting machine, and finally tested for tensile strength and elongation with a universal testing machine. The tensile strength of the copper foil reached 48kgf / mm 2 , the elongation can reach 6%. In this embodiment, the copper foil after the mother roll is rolled off is placed in an oxygen-free environment for heat treatment. After the heat treatment, the tensile strength is 46kgf / mm 2 , the elongation reaches 9.5%.

[0038] Comparative Example 1: Comparative Example 1 provides a process for manufacturing a copper foil, comprising the following steps: Step 1: Prepare copper sulfate electrolyte. Add appropriate amount of sulfuric acid to the treated copper wire in the copper dissolving tank to react and obtain copper sulfate electrolyte. The electrolyte is filtered and purified to obtain pure electrolyte. The sulfuric acid concentration in the pure electrolyte is 95g / L~120g / L, the copper ion concentration is 85g / L~100g / L, the chloride ion concentration is 10mg / L~50mg / L, and the electrolyte temperature is 50℃~65℃; Step 2: adding a brightener, a leveling agent and a wetting agent into an electrolyte, wherein the electrolyte contains 10ppm-12ppm of an additive of a brightener, 2ppm-4.8ppm of an additive of a leveling agent, 1ppm-3.6ppm of an additive of a cellulose type, and 1ppm-3.6ppm of an additive of a polyether type, and the above additives are mixed with the copper sulfate electrolyte; Step 3: The mixed copper sulfate electrolyte is transported to each foil machine for electrolytic foil production. After the foil is produced, samples are taken to test whether the physical properties are qualified. If qualified, normal production will be carried out. If unqualified, adjustments will be made. Step 4: An anti-oxidation device is provided during the foil production process of the foil production machine to perform anti-oxidation treatment on the produced copper foil; Step 5: produce a roll of mother roll copper foil, and place it in an air environment for heat treatment after unwinding; the heat treatment temperature is: keep the copper foil in a heat treatment furnace at 90°C for 40 hours; Step 6: The copper foil that has passed the heat treatment is sent to the slitting machine for slitting, and is packaged and stored after passing the quality inspection; After testing, the raw foil samples were placed in an oven and baked at 150°C for 10 minutes, cut into 100mm×50mm samples with a sampling plate, and cut into 4 100mm×15mm strips with a cutting machine. Finally, the tensile strength and elongation were tested with a universal testing machine. The tensile strength of the copper foil reached 34kgf / mm 2, the elongation can reach 5%. After the mother roll is rolled off, it is placed in an air environment for heat treatment. After heat treatment, the tensile strength is 33kgf / mm 2 , the elongation reaches 5%.

[0039] Comparative Example 2: Comparative Example 2 provides a process for manufacturing a copper foil, comprising the following steps: Step 1: Prepare copper sulfate electrolyte. Add appropriate amount of sulfuric acid to the treated copper wire in the copper dissolving tank to react and obtain copper sulfate electrolyte. The electrolyte is filtered and purified to obtain pure electrolyte. The sulfuric acid concentration in the electrolyte is 95g / L~120g / L, the copper ion concentration is 85g / L~100g / L, the chloride ion concentration is 10 mg / L~50mg / L, and the electrolyte temperature is 50℃~65℃; Step 2: adding a brightener, a leveling agent and a wetting agent into an electrolyte, wherein the electrolyte contains 10ppm-12ppm of an additive of a brightener, 2ppm-4.8ppm of an additive of a leveling agent, 1ppm-3.6ppm of an additive of a cellulose type, and 1ppm-3.6ppm of an additive of a polyether type, and the above additives are mixed with the copper sulfate electrolyte; Step 3: The mixed copper sulfate electrolyte is transported to each foil machine for electrolytic foil production. After the foil is produced, samples are taken to test whether the physical properties are qualified. If qualified, normal production will be carried out. If unqualified, adjustments will be made. Step 4: An anti-oxidation device is provided during the foil production process of the foil production machine to perform anti-oxidation treatment on the produced copper foil; Step 5: After producing a roll of mother roll, it is placed in an oxygen-free environment for heat treatment process; the heat treatment temperature, in the first stage, is raised to 90°C within 3 to 5 hours, and then the copper foil is kept warm in the heat treatment furnace for 10 hours; in the second stage, the copper foil is raised to 130°C within 3 to 5 hours, and then the copper foil is kept warm in the heat treatment furnace for 10 hours; Step 6: The copper foil that has passed the heat treatment is sent to the slitting machine for slitting, and then packaged and stored after passing the quality inspection.

[0040] After testing, the raw foil samples were placed in an oven and baked at 150°C for 10 minutes, cut into 100mm×50mm samples with a sampling plate, cut into 4 100mm×15mm strips with a cutting machine, and finally tested for tensile strength and elongation with a universal testing machine. The tensile strength of the copper foil reached 34kgf / mm 2 , the elongation can reach 5%. After the mother roll is rolled off, the copper foil is placed in an oxygen-free environment for heat treatment. After heat treatment, the tensile strength is 33kgf / mm 2 , the elongation reaches 6.5%.

[0041] The data of the above embodiments and comparative examples are shown in the following table:

[0042] It can be seen from the above table that the grain refiner in the additive of the present invention can improve the tensile strength and elongation of copper foil. The heat treatment in an oxygen-free environment described in the present invention is very effective in improving the elongation of lithium battery copper foil, with an improvement of 2%-3%.

[0043] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0044] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A process for manufacturing an ultra-thin copper foil with high mechanical properties, characterized in that: The following steps are involved: Step S1: placing the treated copper wire into a copper dissolving tank, then adding an appropriate amount of sulfuric acid into the copper dissolving tank for reaction to obtain a copper sulfate electrolyte, and the obtained copper sulfate electrolyte is subjected to a series of filtration and impurity removal purification to obtain a pure copper sulfate electrolyte; Step S2: adding a series of high-resistance and high-ductility additives to the pure copper sulfate electrolyte and performing a mixing process; Step S3: transporting the mixed copper sulfate electrolyte to a foil production machine for electrolytic foil production; Step S4: an anti-oxidation device is provided during the foil production process of the foil production machine to perform anti-oxidation treatment on the produced copper foil; Step S5: After producing a roll of mother roll copper foil, place it in an oxygen-free environment for heat treatment; Step S6: The copper foil that has passed the heat treatment process is sent to a slitting machine for slitting.

2. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 1, characterized in that: In the step S2: the high resistance and high ductility series additives include: brightener, leveler, wetting agent and grain refiner.

3. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 2, characterized in that: The mass concentration ratio of the brightener, the leveler, the wetting agent and the grain refiner is 1:0.2-0.4:0.1-0.3:1-1.

5.

4. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 2, characterized in that: The brightener is an organic substance containing a sodium sulfonate group; the organic substance containing a sodium sulfonate group is one of polyisothiourea propanesulfonic acid inner salt, sodium 3-mercapto-1-propanesulfonate, sodium N, N-dimethyldithioformamide propane sulfonate and sodium polydisulfide propane sulfonate.

5. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 2, characterized in that: The leveling agent is one of a collagen polymer and an amine organic substance.

6. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 5, characterized in that: The wetting agent is a surfactant such as cellulose and polyether.

7. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 2, characterized in that: The wetting agent is specifically one of hydroxymethyl cellulose, hydroxyethyl cellulose, diethylene glycol dimethyl ether, ethylene glycol butyl ether and triethylene glycol divinyl ether.

8. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 2, characterized in that: The grain refiner is one of cyclic sodium disulfide propane sulfonate, phenyl sodium polydisulfide propane sulfonate, rare earth salt, thiourea and thiourea organic matter.

9. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 1, characterized in that: The step S5 specifically includes: producing a roll of mother roll copper foil and placing it into a heat treatment furnace after unwinding, making the heat treatment furnace an oxygen-free environment, and then setting two stages of heat treatment process, and finally slowly cooling it in the heat treatment furnace.

10. The manufacturing process of the ultra-thin copper foil with high mechanical properties according to claim 9, characterized in that: The two-stage heat treatment process includes: in the first stage, the copper foil is heated to 60°C to 90°C within 3h to 5h, and then the copper foil is kept warm in the heat treatment furnace for 0.5h to 30h; in the second stage, the copper foil is heated to 120°C to 150°C within 3h to 5h, and then the copper foil is kept warm in the heat treatment furnace for 1h to 40h.

Citation Information

Patent Citations

  • Preparation method of bright fine-grain copper foil

    CN114959804A

  • Preparation method of high-strength electrolytic copper foil

    CN116876045A

  • Electrolytic copper foil additive for high-tensile lithium battery, electrolytic copper foil and preparation method

    CN118086989A

  • Additive for lithium battery copper foil with extremely low roughness and high elongation and preparation method of copper foil

    CN118621393A

  • Additive for electroylite solution of electroplating process for copper coating with high elongation and electroylite solution of electroplating process for copper coating with high elongation comprising the same

    KR1020130077240A